Corporate social responsibility (CSR) in the service industry: a systematic review - Zhu, Jinsheng Jason; Liu, Zhiyong; Shen, Xiaoping; Shan, Ling; Zhang, Xianchu (Frontiers in Environmental Science, 2023)
The objective of the current study is to perform a systematic review to the published articles upon the advancement of corporate social responsibility (CSR) in the service sector. This article analyzes the bibliometric information of the CSR-related articles linked to the service sector. The existing literature on CSR in the service industry were derived from the online SCOPUS indexing dataset. Through completing a systematic review on existing academic articles, the current paper identifies the nations, universities/institutions, prolific researchers, high-profile journal that contributed to the advancement of CSR theory and practical applications. Moreover, the analytical graphs and bibliometric coupling shown the keyword co-occurrence to depict the academic relationship on the CSR advancement in the service industry. The systematic review adds to an in-depth knowledge of the progression behind CSR in the corporate environment and extends the CSR nexus researches.